Una metodología para auditar tecnologías de información (Tercera parte) - Plata Sánchez, David; Ponce Casanova, Eduardo Hilario (My University, 2013)
Una metodología para auditar tecnologías de información (Tercera parte)
Una metodología para auditar tecnologías de información (Tercera parte)
Keywords: Una metodología para auditar tecnologías de información (Tercera parte)